Hubungan Pilihan Bidang Studi dengan Kecerdasan Mahasiswa Jurusan Teknik Grafika dan Penerbitan - Fitri Nur Ardiantika; Mohammad Fauzy; Azhmy Fawzi MY; Djony Herfan (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2023)
Intelligence is an individual's ability to solve problems, create products and works in a context naturally. Every year the Department of Graphic Engineering and Publishing, which has four study programs, accepts new students. Whether the influence of intelligence is large or small is very important because intelligence is one of the predictors of determining a person's choice of field of study. The aim and benefit of this research is to see a person's potential in choosing a study and career. This method helps to see a person's competencies in a career range that is an opportunity for him. The research method used is a survey research method. The research was conducted on a number of samples purposively. From the eight dimensions of Plural Intelligence, they are Mathematical, Interpersonal, Intrapersonal, Musical, Naturalistic and Kinesthetic, Language and Visualization Intelligence can be predictors in determining the choice of study program. For graphic design study program voters, the first dimension is Visualization, for Publishing study program voters, the first dimension is Interpersonal, and for Graphic Engineering and TICK Study Program voters, it is Naturalistic. Keywords: Multiple Intelligence, Students, Program, Study